2016
DOI: 10.1111/cei.12860
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood T helper type 17 frequency shows an inverse correlation with disease activity and magnetic resonance imaging-based osteitis and erosions in disease-modifying anti-rheumatic drug- and steroid-naive established rheumatoid arthritis

Abstract: An increased expansion of T helper type 17 (Th17) cells in the synovium has been shown to play a key role in cartilage and bone destruction in rheumatoid arthritis (RA). Because the correlation of the peripheral blood helper T cell subsets and various inflammatory cytokines with the magnetic resonance imaging (MRI)-based parameters have not been studied adequately to date, we sought to look for the same in this study. RA patients with disease duration less than 36 months, disease-modifying anti-rheumatic drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…We found that the abundance of Escherichia-Shigella, Monoglobus, and Lachnospira increased while that of Intestinibacter and Prevotella decreased with disease activity in RA. An increase in RA disease activity was shown to be associated with elevated levels of TNF-α and IFN-γ, a higher Th17 count, and altered Treg balance (i.e., Th17/Treg and Th2/Treg ratios) (Edavalath et al, 2016). IL-6, IL-17, and IL-10 levels were higher in RA patients than in HCs and IL-17 and IL-10 were positively correlated with DAS28 score, suggesting that these cytokines can serve as markers for disease outcome and inflammatory response (Ge et al, 2015;Marwa et al, 2017;Dhaouadi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the abundance of Escherichia-Shigella, Monoglobus, and Lachnospira increased while that of Intestinibacter and Prevotella decreased with disease activity in RA. An increase in RA disease activity was shown to be associated with elevated levels of TNF-α and IFN-γ, a higher Th17 count, and altered Treg balance (i.e., Th17/Treg and Th2/Treg ratios) (Edavalath et al, 2016). IL-6, IL-17, and IL-10 levels were higher in RA patients than in HCs and IL-17 and IL-10 were positively correlated with DAS28 score, suggesting that these cytokines can serve as markers for disease outcome and inflammatory response (Ge et al, 2015;Marwa et al, 2017;Dhaouadi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the levels of IL‐17, IL‐21, and IL‐23 were increased in RA patients, whereas the yields of IL‐6, IL‐17, and IL‐21 were higher in active RA compared with inactive RA . However, the frequency of Th17 cells in the peripheral blood suggested an inverse correlation with the disease activity in RA patients who were naive to steroids and disease‐modifying antirheumatic drugs, which was a paradoxical result . Given the complexity of Th17 cell biology and plasticity, the conflict regarding the function of Th17 cells in RA might be rational.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of circulatory Th17 cells was elevated compared to healthy controls in female patients but showed no significant correlation with disease activity in either sex. In contrast, previous studies have shown negative associations between circulating Th17 cells and disease activity measures in DMARD-naive RA patients with a mean disease duration of 10 and 21 months, respectively [ 26 , 27 ]. However, the surface markers used to categorize the T cell subsets in these studies were different from ours.…”
Section: Discussionmentioning
confidence: 82%